Tenth of december eaudiobook Stories. - Saunders, George (Random House Audio, 2013)
NEW YORK TIMES BESTSELLER • NATIONAL BOOK AWARD FINALIST • NAMED ONE OF TIME ’S TEN BEST FICTION BOOKS OF THE DECADE • NAMED ONE OF THE BEST BOOKS OF THE DECADE BY ENTERTAINMENT WEEKLY AND BUZZFEED • NAMED ONE OF THE TEN BEST BOOKS OF THE YEAR BY THE NEW YORK TIMES BOOK REVIEW One of The New York Times ’s 100 Best Books of the 21st Century NAMED ONE OF THE BEST BOOKS OF THE YEAR BY People • The New York Times Magazine • NPR • Entertainment Weekly • New York • The Telegraph • BuzzFeed • Kirkus Reviews • BookPage • Shelf Awareness One of the most important and blazingly original writers of his generation, George Saunders is an undisputed master of the short story, and Tenth of December is his most honest, accessible, and moving collection yet. In the taut opener, “Victory Lap,” a boy witnesses the attempted abduction of the girl next door and is faced with a harrowing choice: Does he ignore what he sees, or override years of smothering advice from his parents and act? In “Home,” a combat-damaged soldier moves back in with his mother and struggles to reconcile the world he left with the one to which he has returned. And in the title story, a stunning meditation on imagination, memory, and loss, a middle-aged cancer patient walks into the woods to commit suicide, only to encounter a troubled young boy who, over the course of a fateful morning, gives the dying man a final chance to recall who he really is. A hapless, deluded owner of an antiques store; two mothers struggling to do the right thing; a teenage girl whose idealism is challenged by a brutal brush with reality; a man tormented by a series of pharmaceutical experiments that force him to lust, to love, to kill—the unforgettable characters that populate the pages of Tenth of December are vividly and lovingly infused with Saunders’s signature blend of exuberant prose, deep humanity, and stylistic innovation. Writing brilliantly and profoundly about class, sex, love, loss, work, despair, and war, Saunders cuts to the core of the contemporary experience. These stories take on the big questions and explore the fault lines of our own morality, delving into the questions of what makes us good and what makes us human. Unsettling, insightful, and hilarious, the stories in Tenth of December —through their manic energy, their focus on what is redeemable in human beings, and their generosity of spirit—not only entertain and delight; they fulfill Chekhov’s dictum that art should “prepare us for tenderness.” GEORGE SAUNDERS WAS NAMED ONE OF THE 100 MOST INFLUENTIAL PEOPLE IN THE WORLD BY TIME MAGAZINE